Makna Warna pada Shio sebagai Implikasi Objek Karya Seni Lukis - Raphael Tan, Joseph; Gulendra, I Wayan; Supriyatini, Sri (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Myth is not fictional like novels that is read every day, however a reality that is believed to have happened and continues to contribute to human life and destiny. Likewise with the myths that exist in the sub-ethnic groups in the world, namely the Chinese. Chinese tribes in the world have various kinds of myths that are consciously embedded in human life. One of the most trusted is about the Chinese zodiacs. In everyday life, the majority of Chinese people believe in and adhere to the Chinese zodiac in all decisions that must be made. Shio is often used in calculating a person's luck in a year, to determine a person's name, to choose a wedding or funeral date and to read a person's character. Not infrequently, often zodiac signs are also used as a benchmark to determine the "compatible" mate. Shio is believed to be something that is able to determine and has its own meaning for everyone who believes in it. The zodiac is symbolized by the animal symbol, starting with the Rat zodiac and the last zodiac being the Pig zodiac. The method that the author took to make this work is a qualitative method with interviews and observations. The author made this work with the aim of understanding more deeply the meaning of colors and the meaning of the zodiac both in terms of astrology, the characteristics of a person's personal nature and psychology.